Effect of Intelligent Selection Training Strategies by Cognitive Impairment Diagnosis and Treatment Instrument on Cognitive Function in Stroke Patients - HUANG Qiuli; OU Jianlin; YAN Jiajian; CHEN Zhuoming (康复学报)
ObjectiveTo analyze the effect of intelligent selection training strategies by cognitive impairment diagnosis and treatment instrument (early dementia intervention system) on cognitive function recovery in stroke patients.MethodsA total of 100 post-stroke patients with cognitive impairment hospitalized in the Rehabilitation Department of the First Affiliated Hospital of Jinan University and the Rehabilitation Department of Dongpu Campus from January 2018 to June 2021 were selected. They were divided into control group and treatment group based on whether they received the intelligent selection training strategies using the cognitive impairment diagnosis and treatment instrument, with 50 patients in each group. In the treatment group, in addition to the conventional medication and limb rehabilitation training, the cognitive impairment diagnosis and treatment instrument (early dementia intervention system) was used to complete the functional evaluation and intervention in the intelligent mode. The intervention training strategy was intelligently selected by the cognitive impairment diagnosis and treatment instrument based on the intelligent evaluation result. The training content included orientation training, memory training, attention training, arithmetic training, communication training, and comprehensive training. The treatment frequency was once a day, with a duration of 20 minutes per session, 5 times per week, for a treatment period of 1 month. The control group received routine medication and limb rehabilitation treatment, with no targeted cognitive training intervention. The cognitive function of patients in the treatment group was evaluated using the mini-mental state examination (MMSE) and the early dementia intervention system intelligent mode before and after one month of training; the cognitive function of the control group was evaluated using MMSE at admission and one month later.ResultsBefore treatment, the statistical analysis of the MMSE evaluation result of the two groups showed that there was no statistically significant difference (P>0.05), in the total score and sub-item score, indicating comparability of cognitive function score between the two groups. After one month of treatment, the total and sub item score of MMSE in the treatment group significantly improved compared to before treatment, and the differences were statistically significant (P<0.05).The total score of MMSE and sub item score of orientation, memory and language abilities in the control group showed significant improvement compared with those before treatment, with statistical significance (P<0.05), while attention, calculation, and recall abilities showed no statistical differences (P>0.05). In the comparison between the two groups, the total score and sub item score of MMSE in the treatment group were significantly higher than those in the control group, and the differences were statistically significant (P<0.05). The intelligent evaluation total score and sub item score of the cognitive impairment diagnosis and treatment system in the treatment group significantly increased after treatment compared with those before treatment, and the differences were statistically significant (P<0.01).ConclusionThe intelligent selection training strategies by the cognitive impairment diagnosis and treatment device (early dementia intervention system) have a positive effect on the cognitive recovery of stroke patients, which can improve the patients' cognitive function in all dimensions, and can be widely promoted and used in clinical practice to the workload of therapists and improve their work efficiency.